Stacking-Racking Analysis: Improving Physics Students' Problem-Solving Skills with ECIRR Learning Model and a Metacognitive Approach - Febriyanti, Tanti; Novia, Hera; Agus Danawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
A preliminary study highlights the persistent challenge of low problem-solving skills among 21st-century students. Therefore, this study examines the ECIRR learning model with a metacognitive approach to improve students' problem-solving skills in static fluid material. The method of this study is quasi-experimental with a one-group pretest-posttest design, enrolling 33 students from class XI at a public high school in Subang City. The Static Fluids Problem Solving Test (SPRING) instrument is used to collect data, which will then be analyzed using the stacking-racking technique. The results showed that ECIRR model learning with a metacognitive approach significantly improved students' problem-solving skills by 2.66 on the logit scale in the moderate category. The highest increase in problem-solving skills was on the plan a solution indicator, and the lowest was on the visualize the problem indicator. The decrease in the level of difficulty of the SPRING instrument indicates that learning has a positive impact. Thus, ECIRR model learning with a metacognitive approach can improve student problem-solving skills in a static fluid material. This study can be strengthened by using a control class to compare the results obtained in the control and experimental groups so that the effectiveness of the intervention can be determined objectively.